2022
DOI: 10.3390/antiox12010006
|View full text |Cite
|
Sign up to set email alerts
|

Interrelation between miRNAs Expression Associated with Redox State Fluctuations, Immune and Inflammatory Response Activation, and Neonatal Outcomes in Complicated Pregnancy, Accompanied by Placental Insufficiency

Abstract: Redox disbalance in placental cells leads to the hyperproduction of reactive oxygen species (ROS), it mediates the dysregulation of the maternal immune tolerance to a semi-allogenic fetus, inducing pro-inflammatory reactions, and it plays a central role in perinatal complications and neonatal disease programming. Microvesicles, which provide transplacental communication between a mother and fetus, contain microRNAs (miRNAs) that are sensitive to oxidative stress (OS) mediators and can control the balance of RO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 76 publications
0
2
0
Order By: Relevance
“…In addition, many studies have shown that disturbance of the redox balance in vivo plays an increasingly important role in sepsis-induced renal injury (45)(46)(47). Endotoxins and renal ischemia/reperfusion injury due to sepsis produce a large number of oxygen radicals and hydroxyl radicals, which can cause lipid peroxidation by degrading polyunsaturated fatty acids in biofilms.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, many studies have shown that disturbance of the redox balance in vivo plays an increasingly important role in sepsis-induced renal injury (45)(46)(47). Endotoxins and renal ischemia/reperfusion injury due to sepsis produce a large number of oxygen radicals and hydroxyl radicals, which can cause lipid peroxidation by degrading polyunsaturated fatty acids in biofilms.…”
Section: Discussionmentioning
confidence: 99%
“…miR-142 , as the core of metabolic reprogramming, directly regulates the glycolysis and immunogenic response of dendritic cells ( Sun et al, 2019 ). miR-127-3p and miR-25-3p can regulate macrophage phenotype and migration and participate in the activation of antioxidant enzymes ( Gusar et al, 2022 ). MiR-21 expression in bone marrow cells can efficiently balance the metabolic reprogramming that causes the cytokine storm in sepsis with the anti-inflammatory mediators that are responsible for inflammation.…”
Section: Discussionmentioning
confidence: 99%